Business laws and regulations : partnership, revised corporation, cooperative law - Domingo, Andrix D. (Itogon Benguet, Philippines : Coaching for Publishing, 2019)
This book is published in the hope that this humble work will be of great help to readers.
Chapter 1. General Provisions -- Chapter 2. Obligations of the partners -- Chapter 3. Dissolution and winding up -- Chapter 4. Limited Partnership -- PARTNERSHIP -- CORPORATION -- COOPERATIVE.
Keywords: PARTNERSHIP -- PHILIPPINE LAW